p16(INK4a) Expression and Immunologic Aging in Chronic HIV Infection - Ribeiro, Susan Pereira; Milush, Jeffrey M.; Cunha-Neto, Edecio; Kallas, Esper G.; Kalil, Jorge; Passero, Luiz Felipe D. [UNESP]; Hunt, Peter W.; Deeks, Steven G.; Nixon, Douglas F.; SenGupta, Devi (Public Library Science, 2016)
Chronic HIV infection is characterized by increased immune activation and immunosenescence. p16(INK4a) (p16) is a member of the cyclin-dependent kinase antagonist family that inhibits cellular proliferation, and its protein expression increases during normal chronological aging. However, some infectious diseases can increase the expression of this anti-proliferative protein, potentially accelerating immunological aging and dysfunction. In order to investigate the immunological aging in HIV patients, p16 protein expression was evaluated by flow cytometry, in T cell subsets in a cohort of chronically HIV-infected patients on and off ART as well as age-matched healthy controls. Results showed that untreated HIV-infected subjects exhibited increased per-cell p16 protein expression that was discordant with chronological aging. ART restored p16 protein expression to levels comparable with HIV-negative subjects in the CD4 compartment, but not in CD8 T cells, which can be an indicative of an irreversible activation/exhaustion status on these cells. Additionally, the frequency of activated CD4+ and CD8+ T cells was positively correlated with p16 expression in CD4+ and CD8+ T cells in untreated subjects. In contrast to healthy controls, untreated HIV-infected individuals had increased p16 levels within the effector memory (T-EM) subset, indicating a possible role for this marker in impaired clonal expansion during antiviral effector function. Taken together, these data demonstrate that chronic HIV infection is associated with elevated expression of the cellular aging marker p16 in T cells. ART restored normal p16 levels in the CD4+ T cell compartment, indicating that use of therapy can be of fundamental importance to normal cell cycling and maintaining immune homeostasis.